(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2020)
The negotiation phase is gaining great importance in investment loans due to the magnitude of the amounts awarded and the need to obtain adequate lending guarantees and the development of better conditions, and this requires that negotiating policy with fixed principles that balance between meeting the demands of customers and maintain market share and achieve profits and avoid defaults and losses the bank, and so I have touched Find the concept of investment loans and procedures for granting and the concept of the negotiation process for the granting of loans. The practical side to ensure the preparation of examination form consists of questions commensurate with the methodology developed by the researchers, were directed to the officials in the sample consisting of the Middle East Investment Bank and Gulf Bank study Altjara.okhls search to conclusions was the most important that negotiations always lead to get the bank to adequate safeguards to recover investment loans and Voidha.kma research found the need to characterized negotiating flexible policies that area not be wide of the diligence of thermoplastic negotiator and that do not intersect with the general policies of the bank.